Access to Finance - Beck, Thorsten; Demirgüç-Kunt, Asli (World Bank, 2012)
Recent data compilations show that many poor and nonpoor people in many developing countries face a high degree of financial exclusion and high barriers in access to finance. Theory and empirical evidence point to the critical role that improved access to finance has in promoting growth and reducing income inequality. An extensive literature shows the channels through which finance promotes enterprise growth and improves aggregate resource allocation. There is less evidence at the household level, however, and on the effectiveness of policies to overcome financial exclusion. The article summarizes recent efforts to measure and analyze the impact of access to finance and discusses the unfinished research agenda.